Reconstruction: 1866-1876 - Ingraham, Irene (My University, 1907)
Introduction: Reconstruction embraces the political problem of restoring the seceeded states to their normal relations with the Union after the suppression of armed resistance to the Laws and to the Constitution. From the very beginning of the Civil War the question of reconstruction was discussed by Northern political leaders; many of them hoped that the war would decide this question; but at the close the northern men were far from any agreement as to the proper manner of restoring the states; Georgia, South Carolina, Virginia, Tennessee, North Carolina, Alabama, Louisiana, Texas, Arkansas, Florida and Missippi to the Union. Discussions concerning reconstruction made clear some of the problems which were to be solved, and gave the opportunity for plans for getting the South back into its former relations to the central government. The political leaders were puzzled by such questions as; What is a state, and are the states in or out of the Union? Could the states be punished for secession, and should the leading force in the reconstruction be Congress, the Exuctive, or the Southern communities? The difficulty of this political problem was further increased by the length and bitterness of the war. The terms of reconstruction that were possible in eighteen hundred sixty-one were impossible in eighteen hundred sixty-six. Every battle that was lost or won, and every case of mistreatment of soldiers was in a certain way a factor in anti-slavery action and in reconstruction.
Citation: Ingraham, Irene. Reconstruction: 1866-1876. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Reconstruction; Post-Civil War; The American South; Nineteenth Century American History; Theses